2003
DOI: 10.1021/jp021712+
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the CH Groups in 1,4-Dioxane Probed by NMR and IR:  Contribution of Blue-Shifting CH···OH2 Hydrogen Bonds

Abstract: H NMR and IR studies were carried out for 1,4-dioxane/H 2 O mixtures over the whole concentration range at temperatures of 1, 25, and 50 °C. 1 H NMR spectra were also acquired for 1,3-dioxane/H 2 O and 4-methyl-1,3-dioxane/H 2 O mixtures. All the chemical shift data were measured by referring to an external reference and corrected using in situ bulk susceptibilities as determined on a unified scale. The results are compared with those previously obtained for dimethyl sulfoxide/H 2 O and acetone/H 2 O mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 49 publications
5
82
1
Order By: Relevance
“…The interaction between the alkyl CÀHb onds of Leu and the water oxygen atoms may be key to the IR and NMR features of the alkyl CÀH bonds in the aliphatic alcohol solutions. As shown in the previous reports, [31,32,40] the oxygen atom of water may also act as ah ydrogen acceptorf or the blue-shifting hydrogen bonds, due to the high electron density of the lone pairs.H ence, the blue-shifting hydrogen bonds between the alkyl CÀHb onds and water mayb ef ormed in the aqueous solution,b ecause the Leu alkyl group is surrounded by water molecules as shown in the SDF.I nf act, as shown in Figure 11,t he interaction between the H d and H d' atoms of the Leu methyl groups and the water oxygen atoms is observed as ah ump at % 2.9 in the g(r) HC Leu -O W for the Leu-water system obtained by the MD simulation. The interaction between the Leu alkyl group and water is gradually weakened in aliphatic alcohol-water solutions, as ar esult of the replacement of water molecules by the alcohola lkyl groups around the Leu alkyl group with increasing x A .C onsequently,t he length of the contracted Leu alkyl CÀ Hb onds is recovered in the aliphatic alcohol solutions with the increasing x A .I tr esults in ar edshift of the Leu CÀHv ibrations with increasing x A .T his also leads to the deshielding of both carbon and hydrogen atoms of the CÀHb onds because of the decrease in the electron densities for both atoms.…”
Section: Solvation Of Leu In Alcohol-water Solutionsmentioning
confidence: 70%
See 1 more Smart Citation
“…The interaction between the alkyl CÀHb onds of Leu and the water oxygen atoms may be key to the IR and NMR features of the alkyl CÀH bonds in the aliphatic alcohol solutions. As shown in the previous reports, [31,32,40] the oxygen atom of water may also act as ah ydrogen acceptorf or the blue-shifting hydrogen bonds, due to the high electron density of the lone pairs.H ence, the blue-shifting hydrogen bonds between the alkyl CÀHb onds and water mayb ef ormed in the aqueous solution,b ecause the Leu alkyl group is surrounded by water molecules as shown in the SDF.I nf act, as shown in Figure 11,t he interaction between the H d and H d' atoms of the Leu methyl groups and the water oxygen atoms is observed as ah ump at % 2.9 in the g(r) HC Leu -O W for the Leu-water system obtained by the MD simulation. The interaction between the Leu alkyl group and water is gradually weakened in aliphatic alcohol-water solutions, as ar esult of the replacement of water molecules by the alcohola lkyl groups around the Leu alkyl group with increasing x A .C onsequently,t he length of the contracted Leu alkyl CÀ Hb onds is recovered in the aliphatic alcohol solutions with the increasing x A .I tr esults in ar edshift of the Leu CÀHv ibrations with increasing x A .T his also leads to the deshielding of both carbon and hydrogen atoms of the CÀHb onds because of the decrease in the electron densities for both atoms.…”
Section: Solvation Of Leu In Alcohol-water Solutionsmentioning
confidence: 70%
“…[33][34][35][36][37][38][39] However,e xperimental results on blue-shifting hydrogen bonds are much scarcer than the theoretical ones. [40][41][42] In particular,b lue-shifting hydrogen bonds have not been observed in the promotion of the secondary structure of biomolecules by TFE and HFIP at the microscopic level, despite the NOE observation of the interactions between the hydrophobic moieties of biomolecules and fluorinated alcohols. [21][22][23][24][25][26] We aimed to clarifyt he solvation structure of the amino acid Leu in aliphatic-alcohol-water andf luorinated-alcohol-water solvents as the first stage of our investigations, because the structures of proteins and peptides are too complex to extract the interactions between their hydrophobic moiety and alcohol molecules by using spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 92%
“…24 It has also been observed that the frequencies of the νCH stretching modes of 1,4-dioxane in water solution increase and the infrared intensities of the modes systematically decrease with increasing concentration of water. 25 This difference has been accounted for by a strong polarization of the water molecules and by the formation of larger hydration clusters formed cooperatively. In the present case, increasing the concentration of enflurane in carbon tetrachloride results in an increase of the polarity of the medium.…”
Section: Optimized Geometry and Nbo Analysis Of The Enflurane Dimermentioning
confidence: 99%
“…However, these small variations have been interpreted in terms of a direct intermolecular interaction, involving the CH 2 group and water, 19 and more recently, like a nonconventional hydrogen bond. 20 Thus, we shall discuss our results as well as the interpretations made in those works in the next section.…”
Section: Resultsmentioning
confidence: 69%
“…Such evidence must be emphasized because the works presented so far, involving DX and water (acting as a Lewis acid), reveal only wavenumber shifts of the C-H and C-O stretching vibrations of DX. 19,20 The second objective is to investigate the influence of the two oxygen atoms of DX on the adduct stoichiometry, and then compare it with that determined for the FA-THF adduct.…”
Section: Introductionmentioning
confidence: 99%